Komunikasi Organisasi pada Divisi Broadcasting Diskominfo Kota Bogor - Wanda Fithriana; Wahyu Budi Priatna (KOMUNIKA, 2026)
The evolution of digital media has prompted government agencies to implement effective organizational communication to support the dissemination of information to the public. This study aims to analyze the organizational communication process and identify the challenges faced by the broadcasting division of the Bogor City Communication and Informatics Agency (Diskominfo). A descriptive qualitative approach was employed, utilizing data collection methods that included participant observation, in depth interviews with two broadcasting division mentors selected via purposive sampling, and a literature review. Data analysis involved data reduction, data presentation, and conclusion drawing grounded in Pace and Faules’ organizational communication theory and supported by concepts from Mandasari and Purba. The findings reveal that organizational communication operates in a structured manner through vertical communication–supported by direct interaction and digital media–with communication patterns that remain flexible to meet work requirements. Challenges identified include delayed responses, unclear directives, and the dynamic nature of the work. This study contributes insights into organizational communication practices with the broadcasting division of a government agency characterized by dynamic work, offering a basis for enhancing the effectiveness of coordination and public information dissemination.